2012
DOI: 10.1158/1078-0432.ccr-11-1789
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase CK2 Protects Multiple Myeloma Cells from ER Stress–Induced Apoptosis and from the Cytotoxic Effect of HSP90 Inhibition through Regulation of the Unfolded Protein Response

Abstract: Purpose: Protein kinase CK2 promotes multiple myeloma cell growth by regulating critical signaling pathways. CK2 also modulates proper HSP90-dependent client protein folding and maturation by phosphorylating its co-chaperone CDC37. Because the endoplasmic reticulum (ER) stress/unfolded protein response (UPR) is central in myeloma pathogenesis, we tested the hypothesis that the CK2/CDC37/HSP90 axis could be involved in UPR in myeloma cells.Experimental Design: We analyzed CK2 activity upon ER stress, the effect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 43 publications
8
70
0
Order By: Relevance
“…Remarkably, CX-4945 efficacy was supported by a clear down modulation of phospho Ser529 RelA and phospho Ser13 CDC37, two well-known CK2 targets. Regarding this latter molecule, since it is an essential co-chaperone of HSP90, it will be interesting to test whether double targeting of HSP90 and CK2 would be synergic in causing NHL cell death, similarly as in MM cells, like we recently demonstrated in in vivo and in vitro models [20]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, CX-4945 efficacy was supported by a clear down modulation of phospho Ser529 RelA and phospho Ser13 CDC37, two well-known CK2 targets. Regarding this latter molecule, since it is an essential co-chaperone of HSP90, it will be interesting to test whether double targeting of HSP90 and CK2 would be synergic in causing NHL cell death, similarly as in MM cells, like we recently demonstrated in in vivo and in vitro models [20]. …”
Section: Discussionmentioning
confidence: 99%
“…The latter encompass B-Chronic Lymphocytic Leukemia (B-CLL) [16, 17], Mantle Cell Lymphoma (MCL) [18] and Plasma Cell Myeloma (PCM) [18, 19]. As for carcinoma cell-lines, in vitro and in vivo pre-clinical studies from our and other groups have indicated that first generation CK2 inhibitors as well as the newer CX-4945 have the potential to be novel therapeutic tools for the treatment of high CK2-expressing B cell tumors [16, 17, 20]. …”
Section: Introductionmentioning
confidence: 99%
“…33, 34 In turn, Hsp90 expression is affected by PERK activity. 34, 35 In addition, the Hsp90–Cdc37 chaperone complex was reported to suppress the autophosphorylation of p38, acting as a specific regulator of the p38 pathway. 20 In agreement with these studies, our data demonstrated that PERK activation by selenite decreased Hsp90 expression and subsequently led to p38 autophosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…PBMC, MM and HS-5 cell lines, primary BMSCs from patients were isolated and cultured as previously described [31, 33, 43]. Malignant CD138 + PCs and healthy B cells were isolated with EasySep™ kits (STEMCELL Technologies, USA), after achieving informed consent according to the declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%